ANALISIS DAN USULAN PERBAIKAN KUALITAS LAYANAN MENGGUNAKAN INTEGRASI METODE SERVQUAL, MODEL KANO DAN QFD DI C&R CAFÉ & RESTO SURABAYA - Faisal Fauzi Abdillah; Yenny Sari; Mochammad Arbi Hadiyat (CALYPTRA, 2018)
C&R & Café Resto Surabaya was one of the café 's restaurants & Surabaya city located on the road of Pucang Anom No. 33. Efforts in providing good service to c ustomers always remain unanswered by the C&R Ca fé & Resto Surabaya. However, the C&R Café & Resto Surabaya have never done the measurement of service quality so that it do not know what is perceived by the customers. In improving the quality of the s ervice, need to know what attributes are s till not s atisfactory to the customer i.e. the gap between satisfaction is received with the expectation of customers, so as to note what the customer wants. The purpose of this research is to know the magnitude of the gap that occurs, specify the attribute priority service and know the improvements done in advance and make a proposal for improvements to the C&R Ca fé & R esto Surabaya. To find out the gap or the magnitude of the GAP that happens to use SERVQUAL method containing 5 dime nsions of s ervice quality that is tangible, reliability, responsiveness, assurance, and emphaty with 26 attributes to measure the quality of service C&R Café & Resto Surabaya. Based on an analysis of the perception gap with the hope that it bri ngs customers to a-26 variable dimensions of tangible, reliability, responsiveness, assurance, and emphaty experience gap. Service attributes to 17th a nd 25th have a mean gap of pe rception and expectations of the customers most negatively of 0.36-and-0.31. Based on the results of the integration method of canoeing and SERVQUAL there are 11 attributes the improved service and repair analysis performed using QFD method so obtained the recommendation given to be repaired first by looking at the value of the importance of the highest standard to make IE how's raw and daily reports the performance of employees with a value of 21%. The proposal fixes for C&R Café & Resto Surabaya, among others, make raw and standard daily reports the performance of employees, giving training on service in the restaurant, providing training to employees and restaurant owners create a reward system, adding tenaga waiters or waitresses, assigning punishment system and set the SOP, increasing employees ' welfare and give employees a fixed contract, make customer complaints and suggestions box rewarding system, applying to employees, the schedule and the standard of cleanliness of the toilet, make the standard of cleanliness of the dining room, in collaboration with the shop owner next door to the parking lot for the results.